Cultural Symbol dan Politik Identitas dalam Pembangunan Kota Sampit - Ma'rufah, Thau'am (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
This study aims to trace the cultural symbols and identity politics that occur in the city of Sampit. This is based on several important things that happened in Sampit. Sampit is a heterogeneous and multicultural city and at the same time there were riots between the Dayak and Madura tribes around 2000, which resulted in the emptying and rejection of Madurese residents. At least in the past two decades, Sampit has turned into a city that displays an identity as a Muslim city with the emergence of urban icons built by local elite leaders. It is interesting to track what exactly is behind the elite officials in the city of Sampit in building these identity symbols and how political symbol culture plays a role in the development of the city of Sampit. The analytical tool used in this study is functional sociology where the emphasis of this study is on actors who provide change in society. The results of this study indicate that several values obsess over Cultural Symbol actions in Sampit, including; First, religious values, one of which orientates the cultural symbol policy is that the Sampit community is moved to worship their Lord and minimize criminal acts that used to occur frequently, such as wild speeding, theft and obscene acts. Secondly, art values, symbols used such as the dome and calligraphy of Asmaul Husna and calligraphy of Allah and Muhammad’s writings are expressions of the architectural art values possessed by the Sampit regent which used to beautify the city of Sampit. Third, Political Interest, every policy carried out by an elite certainly cannot be separated from political interests, the Sampit regent is no exception, which in this case is to perpetuate his power, bearing in mind that the regent is in power for two periods untill 2020.